Getting to Know the Gut Microbial Diversity of Metropolitan Buenos Aires Inhabitants - Penas Steinhardt, Alberto (2019)
Fil: Penas Steinhardt, Alberto. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.